Effects of Alumina on Cristobalite Crystallization and Properties of Silica-Based Ceramic Cores. Issue 2 (February 2017) - Liang, J.J.; Lin, Q.H.; Zhang, X.; Jin, T.; Zhou, Y.Z.; Sun, X.F.; Choi, B.G.; Kim, I.S.; Do, J.H.; Jo, C.Y.
Abstract : In this work, the influences of alumina addition on cristobalite crystallization and properties of injection molded silica-based ceramic cores were investigated. X-ray diffraction (XRD) was used to characterize phase transformations in the samples, and the XRD result indicated that the addition of alumina promoted crystallization of fused silica during sintering at 1180–1220 °C and thus increases the amount of cristobalite. The increased amount of cristobalite as well as alumina addition led to much more thermal dilation due to their higher coefficients of thermal expansion than that of fused silica. The flexural strengths at room temperature and 1500 °C were tested, and it was shown that alumina addition could not affect room temperature strength, but decreased the flexural strength at 1500 °C. In addition, deflection resistance during heating to high temperatures was investigated, and the result indicated that alumina addition speeded up high temperature softening of the samples. XRD and scanning electron microscopy equipped with energy dispersive spectrometry (SEM/EDS) analysis suggested that this softening behavior was related with viscous flow sintering which could be accelerated by the reaction of alumina and silica with a product of mullite.